Effects of cathode doping on 3D printed continuous carbon fiber structural battery composites by UV-assisted coextrusion deposition. (November 2021) - Pappas, John M; Thakur, Aditya R; Dong, Xiangyang
Structural battery composites are capable of significant system level mass and volume reductions not possible with separate battery and structural components by simultaneously carrying mechanical loads and storing electrical energy. The ability to 3D print lithium-ion structural batteries in arbitrary geometries would not only allow a flexible battery design but also facilitate its implementation as a structural component. This study presents a new 3D carbon fiber structural battery composite 3D printed by an ultraviolet (UV)-assisted coextrusion deposition method. With individual carbon fibers coated by solid polymer electrolyte (SPE) and dispersed within cathode doped matrix, energy storage is achieved in micro-battery cells at the fiber level within the 3D printed structural battery composite. The 3D printed structural battery composites with various complex geometries are demonstrated by successfully powering up LEDs. The SPE coating and cathode doping effect on microstructure, printability, mechanical and electrochemical properties are further characterized and investigated. A trade-off between printability and electrochemical performance is observed due to hindered curing by the doped cathode materials. The obtained electrochemical and mechanical performance is comparable to the carbon fiber based structural battery composites fabricated by conventional lay-up processes. These well demonstrate the great potentials of the proposed 3D printing method in rapidly fabricating functional structural battery composite components with complex geometries.